Pensamiento crítico en la diversidad cultural educativa - Ortega Cobos, Jennifer Alejandra (2025)
The present study, called "Critical Thinking in Educational Cultural Diversity," looks at a key problem for seventh-grade students. These students find it hard to move past stereotypes and unfair systems because they do not question common beliefs. Without open talk between cultures, students do not know much about their own or others' habits, traditions, and views. This makes it hard to build knowledge together. The goal of the study is to see how seventhgrade students at Fe Elementary School develop critical thinking when there is cultural diversity. The study used a qualitative approach and a dialogic decision-making design. The research was exploratory, descriptive, and propositional. It was cross-sectional in time and took place in both field and documentary-bibliographic settings. The study used phenomenological and action research methods. The main group had 84 middle basic education students from Fe y Alegría School. Of these, 24 seventh-grade students were key informants. Data were collected using various techniques and instruments. The study concludes that seventh-grade students at Fe y Alegría Basic Education School are still developing critical thinking. They continue to face stereotypes and power structures without questioning existing ideologies. The lack of intercultural dialogue limits their understanding of different practices, traditions, and perspectives. This constrains collective knowledgebuilding.